Pengaruh Model pembelajaran Contextual Teaching And Learning (CTL) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII SMP Negeri 5 Pematangsiantar Pada Materi Sistem Persamaan Linear Dua Variabel - Elisabeth Veronika Simanjuntak; Belsasar Sihombing; Christa Voni Roulina (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2023)
This research aims to describe and analyze the mathematical problem solving abilities of class VIII students at SMP Negeri 5 Pematangsiantar on two-variable linear equation systems material, with treatment in the form of a Contextual Teaching And Learning (CTL) learning model. The approach taken in this research is a quantitative approach. Sampling was carried out using a simple random sampling technique. The research subjects were class VIII-6, totaling 30 people. The data collection technique in this research is in the form of a test to determine students' mathematical problem solving abilities in the research process carried out. Data analysis techniques were carried out using normality tests and hypothesis tests. From the results of data analysis, the results of students' mathematical problem solving abilities showed that the average pre-test score was 54336 and the average post-test score = 79,400. A significant value (2-tailed) 0.000 < 0.05 indicates that there is a significant difference between the initial and final variables. Thus, the independent variable has a significant effect on the dependent variable. So it can be concluded that by applying the Contextual Teaching And Learning CTL learning model) it can improve the mathematical problem solving abilities of class VIII students at SMP Negeri 5 Pematangsiantar on the material of two-variable linear equation systems.